Malaysian experience of rainfall induced related disaster - Mohamad, Edy Tonnizam (2015)
This paper presents the experience of rainfall-induced related disaster experienced by Malaysia. Landslides and Slope Failures in Malaysia are much related to heavy downpour and had claimed lives of 611 peoples in 60 recorded landslides. In addition, the most recent great flood in December 2014 had recorded losses of more than RM 2 billion and affected more than 200,000 people. Together with the rise of sea level and its negative effects on living things, one of the direct effects of the climatic change is possibly the increased frequency of heavy rains. Obviously heavy rain in mountainous regions trigger slope failures and induced tragedies. The present paper addresses the basic strategy to cope with this ongoing adverse situation from the viewpoint of disaster mitigation.